Causes and Effect High Hemodialysis Patients Not Served in Bangil Hospital - Fitri Indahyanti; Tatong Harijanto; Arma Roosalina (Universitas Muhammadiyah Yogyakarta, 2020)
One of the excellent services in Bangil Regional Hospital is the hemodialysis unit service, from 2017 to August 2019, the number of patients not served by hemodialysis is still high. This study aims to determine the factors causing the high number of patients who are not served by hemodialysis. Type of descriptive qualitative research. Primary data were obtained from interviews with a sample of six people consisting of the head of the hemodialysis unit, the head of the service sector, the head of the outpatient service section, the head of the inpatient services section, the head of the education and training section and the head of the personnel subdivision. Secondary data obtained from the study of documents, observations, and literature. Data was taken from August to October 2019, and fishbone analysis was conducted. The results of the study found eight causative factors, namely there is no policy (policy) for the development of hemodialysis units, no dialysis expert general practitioners, lack of skilled dialysis nurses, no 24-hour service policy and cito hemodialysis, limited space capacity and hemodialysis machines, budget Hemodialysis training and development has not been prioritized, and hemodialysis training is waiting a long time.